2019
DOI: 10.1186/s12864-019-6284-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-miRNA interaction prediction through sequence-derived linear neighborhood propagation method with information combination

Abstract: BackgroundResearchers discover lncRNAs can act as decoys or sponges to regulate the behavior of miRNAs. Identification of lncRNA-miRNA interactions helps to understand the functions of lncRNAs, especially their roles in complicated diseases. Computational methods can save time and reduce cost in identifying lncRNA-miRNA interactions, but there have been only a few computational methods.ResultsIn this paper, we propose a sequence-derived linear neighborhood propagation method (SLNPM) to predict lncRNA-miRNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…The nearest neighborhood information of biological entities in the association network can improve the prediction performance (Zhang et al, 2019a,b,c). For example, Zhang et al (2019a), Zhang et al (2019b), and Zhang et al (2019c) used neighborhood information and effectively found microRNA-disease associations, drug-drug interactions and long non-coding RNA-miRNA interactions. Therefore, we integrated neighborhood information to the above optimization model and built the final LMFNR model by Equation 14:…”
Section: Mda Prediction Based On Lmfnrmentioning
confidence: 99%
“…The nearest neighborhood information of biological entities in the association network can improve the prediction performance (Zhang et al, 2019a,b,c). For example, Zhang et al (2019a), Zhang et al (2019b), and Zhang et al (2019c) used neighborhood information and effectively found microRNA-disease associations, drug-drug interactions and long non-coding RNA-miRNA interactions. Therefore, we integrated neighborhood information to the above optimization model and built the final LMFNR model by Equation 14:…”
Section: Mda Prediction Based On Lmfnrmentioning
confidence: 99%
“…In the future, we will further consider deep learning-based models to better integrate diverse biological data and improve predictive performances. Finally, the linear neighborhood propagation method (Zhang et al, 2018a(Zhang et al, , 2019c) may be efficiently applied to SMiR association prediction.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…There are complex interactions between lncRNAs and miRNAs, such as adsorption, inhibition, competition, etc., [19]. Recently, more and more lncRNA-miRNA interactions have been disclosed by many research efforts [20], [21]. Therefore, in cancer classification, the pure study of the independent regulation of one or more NCGs on PCGs, without considering the interaction between different types of NCGs and the joint regulation of the NCGs' interaction on PCGs, will lead to the loss of key association information for classification and the incapacity of accurately reappearing the complex mechanism of cancer development.…”
Section: A Dataset Constructionmentioning
confidence: 99%